Inheritance Rights Of Children Who Have Changed Sex Reviewed From The Civil Code And Islamic Inheritance Law - M. Dimas Ravi; Muh. Jufri Ahmad (Mimbar Yustitia: Jurnal Hukum dan Hak Asasi Manusia)
This study discusses the problem of inheritance law for children (transvestites) from the perspective of the Civil Code (KUH Perdata) and Islamic law. The Civil Code (KUH Perdata) and Islamic law. The phenomenon of transsexuals is a complex problem, both socially, religiously, and legally, because it involves changes in gender identity that have implications for legal status and inheritance rights. This study aims to analyze how inheritance law in Indonesia, both in the Civil Code and Islamic law, accommodates the rights of transvestites as heirs. The method used is normative juridical with a statutory approach and a conceptual approach. statutory approach and a conceptual approach. This study examines positive law in Indonesia, the fatwa of the Indonesian Ulema Council (MUI), and the views of scholars on the phenomenon of transsexuals. transsexual phenomenon. In civil law, inheritance rights are regulated based on blood relations or marriage, without considering changes in gender. Meanwhile, in Islamic law, gender reassignment is seen as problematic because it contradicts the basic teachings of the provisions of Allah. because it contradicts the basic teachings of the provisions of Allah. The MUI fatwa states that deliberate sex change is haram, except for cases that require confirmation. This study reveals a legal vacuum related to specific regulations regarding the legal status of transsexuals in inheritance in Indonesia. In the Civil Code, transsexuals are recognized based on changes in population data that are validated by the court. However, in Islamic law, the inheritance rights of transsexuals are not recognized.